2002
DOI: 10.1046/j.1365-3040.2002.00949.x
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of xylem sap amino acid concentrations in conjunction with whole tree transpiration estimates spring N remobilization by cherry (Prunus avium L.) trees

Abstract: Prunus avium trees were grown in sand culture for one vegetative season with contrasting N supplies, in order to precondition their N storage capacities. During the spring of the second year a constant amount of 15 N was supplied to all the trees, and the recovery of unlabelled N in the new biomass production was used as a direct measure of N remobilization. Destructive harvests were taken during spring to determine the pattern of N remobilization and uptake. Measurements of both xylem sap amino acid profiles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
50
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(59 citation statements)
references
References 44 publications
9
50
0
Order By: Relevance
“…Under high-RH conditions, STA EPS62e cells (see Materials and Methods) maintained initial population levels or slightly increased on flowers, around 10 8 CFU flower Ϫ1 , in Passe Crassane and Abate Fetel pear flowers (Fig. 2).…”
Section: Resultsmentioning
confidence: 96%
“…Under high-RH conditions, STA EPS62e cells (see Materials and Methods) maintained initial population levels or slightly increased on flowers, around 10 8 CFU flower Ϫ1 , in Passe Crassane and Abate Fetel pear flowers (Fig. 2).…”
Section: Resultsmentioning
confidence: 96%
“…(MALAGUTI et al, 2001) and cherry trees (Prunus avium L.) (MILLARD et al, 2006;GRASSI et al, 2002), reaching maximum values near the budding stage. MALAGUTI et al (2001) reported that, 106 days prior to budding, the concentrations of Asn, Asp, and Gln were 287, 109, and 101μg ml -1 sap, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…In this manner, the initial growth of buds becomes almost entirely dependent on the N reserves of vegetative tissues, since the root system is only activated after the initiation of growth by new sprouts. Although few studies have described the dynamics of the process in detail, it is evident that the remobilization of N occurs before absorption by roots, at least in some species, such as apple (DONG et al, 2001), pear (QUARTIERI et al, 2002), peach (RUFAT & DeJONG, 2001) and cherry trees (GRASSI et al, 2002). One plausible explanation for the remobilization of N from vegetative parts before absorption from soil is the fact that air temperature increases more quickly than soil temperature at the beginning of spring, when rates of N mineralization and availability are still very low (MILLARD & GRELET, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Information on the effectiveness of foliar N applications in sweet cherry is lacking. To study the canopy distribution of N applied as urea foliar sprays, an experiment using a "Bing"/"Gisela root absorption begins three weeks later, indicating a dependence on the N reserves early in the season (Grassi et al, 2002;Grassi et al, 2003;Ouzounis and Lang, 2011). N storage reserves represent approximately 50% of the N used for new growth during early spring.…”
Section: Introductionmentioning
confidence: 99%
“…N storage reserves represent approximately 50% of the N used for new growth during early spring. The remaining N comes from root absorption and soil uptake (Grassi et al, 2002;Grassi et al, 2003;Azarenko and Chozinski, 2005).…”
Section: Introductionmentioning
confidence: 99%